Identification of genetic loci for growth and stem form traits in hybrid Liriodendron via a genome-wide association study - Fengchao Zhang; Xiao Liu; Hui Xia; Hainan Wu; Yaxian Zong; Huogen Li (Forestry Research)
A key objective of forest tree breeding programs is to enhance traits related to growth and stem form, to cultivate plantations that exhibit rapid growth, straight trunks with minimal taper, and superior wood quality to meet the demands of modern timber production. Notably, Liriodendron species exhibit notable heterosis in interspecies hybrids, with hybrid Liriodendron displaying rapid growth rates, straight trunks, and wide adaptability. However, the genetic architecture underlying growth and stem form traits remains unclear, hindering the progress of genetic improvement efforts. Genome-wide association study (GWAS) emerges as an effective approach for identifying target genes and clarifying genetic architectures. In this study, a comprehensive analysis was conducted using an artificial population of 233 hybrid progeny derived from 25 hybrid combinations and resequenced to obtain genome-wide single nucleotide polymorphism (SNP) and insertion and deletion (InDel) variants. After filtering, a total of 192,972 SNP loci and 60,666 InDel loci were obtained, which were subsequently analyzed for associations using the R package GAPIT. We identified 97 significant SNP loci and 58 significant InDel loci (−Log10(P) ≥ 4.50), respectively, culminating in the identification of 161 candidate genes. The functions of these candidate genes were annotated, revealing potential associations between Lchi_2g03172 and Lchi_10g19986 genes with the growth of hybrid Liriodendron, and highlighting the potential influence of the Lchi_16g30522 gene on the growth and branching of hybrid Liriodendron. Overall, this study serves as a foundational step towards unraveling the genetic architecture underpinning growth and stem form in Liriodendron plants.